2006
DOI: 10.1007/s00432-006-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among breast cancer patients undergoing autologous breast reconstruction versus breast conserving therapy

Abstract: Our study demonstrated that autologous tissue breast reconstruction in breast cancer patients did not affect adversely the health-related quality of life compared to breast conserving therapy when the quality of life is assessed by the standardized questionnaire SF-36. In particular, the physical function is not reported to be significantly influenced negatively by the more extensive surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Findings from some previous studies are in agreement with the present results 2,12,15,36. Other studies, however, have identified differences in QOL in breast cancer survivors as a function of the type of surgical procedure 16,19,22,23,37. Dian et al19 investigated QOL using the SF-36 questionnaire and reported better scores in physical functioning in women submitted to breast reconstruction compared with those submitted to conservative surgery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Findings from some previous studies are in agreement with the present results 2,12,15,36. Other studies, however, have identified differences in QOL in breast cancer survivors as a function of the type of surgical procedure 16,19,22,23,37. Dian et al19 investigated QOL using the SF-36 questionnaire and reported better scores in physical functioning in women submitted to breast reconstruction compared with those submitted to conservative surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies that investigated these parameters reported conflicting results, and the majority of these studies were conducted in developed countries. 3,5,12,17,19,29 The present study reports findings in a cohort of Brazilian breast cancer survivors.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Breast-conserving therapy included primary breast-conserving surgery as well as breast reconstruction as these two techniques have been reported to yield comparable results with respect to QOL (Cocquyt et al 2003;Dian et al 2007;Nano et al 2005).…”
Section: Type Of Surgerymentioning
confidence: 98%